2014
DOI: 10.1186/1471-2202-15-7
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decline in cognitive control: the role of fluid intelligence and processing speed

Abstract: BackgroundResearch on cognitive control suggests an age-related decline in proactive control abilities whereas reactive control seems to remain intact. However, the reason of the differential age effect on cognitive control efficiency is still unclear. This study investigated the potential influence of fluid intelligence and processing speed on the selective age-related decline in proactive control. Eighty young and 80 healthy older adults were included in this study. The participants were submitted to a worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 58 publications
6
34
0
Order By: Relevance
“…Likewise, and as it could have been expected from several previous studies (Albinet et al, 2012;Cona et al, 2013;Manard et al, 2014;Salthouse, 1992;Salthouse, 1993;Salthouse, 1994a;Salthouse, 1994b;Salthouse, 1996;Salthouse & Babcock, 1991;Salthouse & Meinz, 1995;Salthouse, 2000;Salthouse et al, 2000), all processing speed variables were predicted by age. Salthouse proposed that perceptual speed is more involved in the relationship between age and cognition than motor speed (Salthouse, 1993;Salthouse, 1994b).…”
Section: Age Effects On Executive Processing Speed and Attentional Tsupporting
confidence: 84%
See 1 more Smart Citation
“…Likewise, and as it could have been expected from several previous studies (Albinet et al, 2012;Cona et al, 2013;Manard et al, 2014;Salthouse, 1992;Salthouse, 1993;Salthouse, 1994a;Salthouse, 1994b;Salthouse, 1996;Salthouse & Babcock, 1991;Salthouse & Meinz, 1995;Salthouse, 2000;Salthouse et al, 2000), all processing speed variables were predicted by age. Salthouse proposed that perceptual speed is more involved in the relationship between age and cognition than motor speed (Salthouse, 1993;Salthouse, 1994b).…”
Section: Age Effects On Executive Processing Speed and Attentional Tsupporting
confidence: 84%
“…Indeed, with advancing age, some changes are also reported in non-executive processes that could influence executive functioning efficiency. Furthermore, there is a general agreement that processing speed decreases with age (Albinet, Boucart, Bouquet, & Auddifren, 2012;Cona et al, 2013;Manard, Carabin, Jaspar, & Collette, 2014;Salthouse, 1992;Salthouse, 1993;Salthouse, 1994a, Salthouse, 1994bSalthouse, 1996;Salthouse & Babcock, 1991;Salthouse & Meinz, 1995;Salthouse, 2000;Salthouse et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…WM is thought of as the brain's capacity to store and manipulate information necessary for successful performance in a given situation (Baddeley and Hitch, 1974) and has received large amounts of interest in the general aging and EEG literature. As such, a number of studies have demonstrated that the amount of items held in WM declines with advancing age (Salthouse and Babcock, 1991), whereas numerous EEG studies have reported age-related reductions of theta, alpha, and gamma activity during WM task engagement (Karrasch et al, 2004;Manard et al, 2014;van de Vijver et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…There are some situations in which one or the other type of control would be most appropriate, depending on factors such as individual characteristics and task situation. Given that older adults have limited processing resources (Craik and Byrd, 1982; Manard et al, 2014), it may be difficult for them to process the cue proactively and maintain the cue information over the delay in the AX-CPT task (Braver et al, 2001). Thus, older adults prefer to rely predominantly on reactive control mechanisms in the AX-CPT task, as they do not require sustained control over extensive time periods.…”
Section: Discussionmentioning
confidence: 99%